Effect of side groups on the properties of silicon‐containing arylacetylene resins. Issue 3 (17th January 2022) - Liu, Xiaotian; Ma, Manping; Li, Chuan; Tang, Junkun; Yuan, Qiaolong; Huang, Farong
Abstract: Four silicon‐containing arylacetylene resins were synthesized by polycondensation of Grignard reagent of m ‐diethynylbenzene with methylethyldichlorosilane, dimethyldichlorosilane, methylphenyldichlorosilane, and diphenyldichlorosilane, respectively. The structures of the resins were verified by nuclear magnetic resonance spectroscopy and Fourier transform infrared (FTIR) spectroscopy. The solubility, crystallinity, and rheological character of the resins were characterized. The curing behavior was traced by differential scanning calorimetry (DSC) and FTIR analyses. The effect of the side groups on the silicon atom on the properties was investigated. The results show that the resins with asymmetrical side groups display better processability (wide processing window) as compared with those with symmetrical side groups. The resin with side phenyl groups shows higher flexural strength but lower thermal stability as compared with those without side phenyl groups. Meanwhile, the side phenyl groups also enhance the temperature at which secondary relaxation occurs. Abstract : The resins with side phenyl groups show high flexural strength but low thermal stability. The resins with asymmetric side groups display the good processability.